Hydrothermal activity recorded in post Noachian‐aged impact craters on Mars. Issue 4 (15th April 2016) - Turner, Stuart M. R.; Bridges, John C.; Grebby, Stephen; Ehlmann, Bethany L.
Abstract: Hydrothermal systems have previously been reported in ancient Noachian and Hesperian‐aged craters on Mars using CRISM but not in Amazonian‐aged impact craters. However, the nakhlite meteorites do provide evidence of Amazonian hydrothermal activity. This study uses CRISM data of 144 impact craters of ≥7 km diameter and 14 smaller craters (3–7 km diameter) within terrain mapped as Amazonian to search for minerals that may have formed as a result of impact‐induced hydrothermal alteration or show excavation of ancient altered crust. No evidence indicating the presence of hydrated minerals was found in the 3–7 km impact craters. Hydrated minerals were identified in three complex impact craters, located at 52.42°N, 39.86°E in the Ismenius Lacus quadrangle, at 8.93°N, 141.28°E in Elysium, and within the previously studied Stokes crater. These three craters have diameters 20 km, 62 km, and 51 km. The locations of the hydrated mineral outcrops and their associated morphology indicate that two of these three impact craters—the unnamed Ismenius Lacus Crater and Stokes Crater—possibly hosted impact‐induced hydrothermal systems, as they contain alteration assemblages on their central uplifts that are not apparent in their ejecta. Chlorite and Fe serpentine are identified within alluvial fans in the central uplift and rim of the Ismenius Lacus crater, whereas Stokes crater contains a host of Fe/Mg/Al phyllosilicates. However, excavation origin cannot be precluded. Our work suggests that impact‐induced hydrothermalism was rare in the Amazonian and/or that impact‐induced hydrothermal alteration was not sufficiently pervasive or spatially widespread for detection by CRISM. Key Points: Mars craters in post Noachian terrains studied with CRISM to determine presence of hydrated minerals Only 3 of 158 craters show clay‐bearing assemblages Impact hydrothermalism possible in two craters